2013
DOI: 10.1155/2013/710290
|View full text |Cite
|
Sign up to set email alerts
|

Five Decades with Polyunsaturated Fatty Acids: Chemical Synthesis, Enzymatic Formation, Lipid Peroxidation and Its Biological Effects

Abstract: I have been involved in research on polyunsaturated fatty acids since 1964 and this review is intended to cover some of the most important aspects of this work. Polyunsaturated fatty acids have followed me during my whole scientific career and I have published a number of studies concerned with different aspects of them such as chemical synthesis, enzymatic formation, metabolism, transport, physical, chemical, and catalytic properties of a reconstructed desaturase system in liposomes, lipid peroxidation, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 62 publications
(57 reference statements)
1
35
0
Order By: Relevance
“…Alterations in dietary PUFA levels, n-3 fatty acids and n-3/n-6 ratio can also affect membrane-linked cellular processes involved in energy metabolism (Hulbert et al, 2005). Research indicates that changes in dietary lipids impact metabolic rate, neuropeptide activity, second messenger generation and gene expression thus affecting several glucose and lipid metabolism pathways; confirming the role of PUFAs as signaling molecules related to growth, development, and energy metabolism (Hulbert et al, 2005; Wei et al, 2010; Catala, 2013). …”
Section: Introductionmentioning
confidence: 84%
“…Alterations in dietary PUFA levels, n-3 fatty acids and n-3/n-6 ratio can also affect membrane-linked cellular processes involved in energy metabolism (Hulbert et al, 2005). Research indicates that changes in dietary lipids impact metabolic rate, neuropeptide activity, second messenger generation and gene expression thus affecting several glucose and lipid metabolism pathways; confirming the role of PUFAs as signaling molecules related to growth, development, and energy metabolism (Hulbert et al, 2005; Wei et al, 2010; Catala, 2013). …”
Section: Introductionmentioning
confidence: 84%
“…The FADS genes ( FADS1, FADS2 and FADS3 ) are fatty acid desaturase genes. The proteins encoded by these genes are key enzymes involved in the the desaturation of n-3 and n-6 polyunsaturated fatty acids as follows: FADS1 desaturates at the delta-5 position [e.g., the conversion of DGLA (20:3n6) to AA (20:4n6)] and FADS2 desaturates at the delta-6 position [e.g., the conversion of LA (18:2n6) to GLA (18:3n6)] [22,46]. FADS3 has non-specific, or currently ill-defined desaturation activity (see also Supplemental Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on placental BeWo cell lines, explants, and rats indicate that at lower doses, omega 3 fatty acid (especially DHA) reduces placental oxidative stress and oxidative DNA damage and increases the levels of resolvins, protectins, and total antioxidant capacity . However, in contrast, free radicals are also known to peroxidize LCPUFA, which is injurious to the cells . A recent human study reported that diets rich in EPA and DHA during pregnancy were unable to reduce inflammatory cytokine levels in the placenta .…”
Section: Regional Development and Function Of The Placenta: Possible mentioning
confidence: 99%